The Anatomy of Ingrid Mattson’s Interpretation of the Qur’an: History, Authority, and Translation Problems - Ahmad Saefudin; Ahmad Rafiq; Marhumah Marhumah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Many contemporary thinkers have introduced various theories in Quranic studies. For example, Fazlur Rahman with double movement theory, Gadamer through a fusion of the horizon, and Abdullah Saeed with contextual interpretation. Meanwhile, Ingrid Mattson’s thoughts on the interpretation of the Koran have not been widely studied by scholars. Mattson has placed the historical context, the personal context of the reader, and the context of the reader's understanding as an integral part of the theory of interpretation. This article wishes to dissect the anatomy of Mattson's interpretation of the Koran. With the historical textual criticism approach popularized by Muhammad Mustafá Azami, this study concludes that apart from historical aspects, the interpretation of the Koran is also strongly influenced by the authority of the rulers at that time, individual charisma (ulama), and the consensus of religious experts. The reduction of God’s message is also very vulnerable to the rampant action of translating the Koran from Arabic into ajam (non-Arabic) language. These three aspects are the constructs of Mattson's thought in his hermeneutical study. Therefore, it is hoped that this academic discourse will add to the style of thinking of scholars in the field of Qur'an studies, which previously have colored contemporary exegesis studies.